Effects of chlorpyrifos on reproductive toxicology of male rats. Issue 9 (30th January 2013) - Sai, Linlin; Li, Xiangxin; Liu, Yanzhong; Guo, Qiming; Xie, Lin; Yu, Gongchang; Bo, Cunxiang; Zhang, Zhenling; Li, Ling
<x xml:space="preserve">Abstract</x> The aim of this study is to investigate the effects of subchronic exposure to chlorpyrifos on reproductive toxicology of male rats. Forty healthy male rats were divided into four groups: three exposure groups and a control group. Chlorpyrifos was administered orally to male rats at 0, 2.7, 5.4, and 12.8mg/kg for 90 days to evaluate the toxic alterations in testicular histology, testicular marker enzyme activities and related genes expression levels, sperm dynamics, and testosterone levels. The body weight and the testis weight of animals did not show any significant changes. Chlorpyrifos brought about marked reduction in testicular sperm counts, sperm motility, and significant growth of sperm malformation rate in exposed males. Histopathological examination of testes showed mild to severe degenerative changes in seminiferous tubules at various dose levels. The levels of testosterone (T) showed a decreasing tendency, and there was a statistical difference between the 5.4, 12.8 mg/kg groups, and the control group. The levels of follicle stimulating hormone (FSH) were significantly increased in 5.4 and 12.8 mg/kg groups, but there were no obvious effects on the levels of luteinizing hormone (LH) and estradiol (E2). A significant increase in the activities of LDH and LDH‐x was observed in chlorpyrifos exposed rats in 5.4 and12.8 mg/kg groups, but the expression levels of related genes had no significant differences between chlorpyrifos exposure groups and the control group. These results suggest that chlorpyrifos has adverse effects on reproductive system of male rats. © 2013 Wiley Periodicals, Inc. Environ Toxicol 29: 1083–1088, 2014.